2019
DOI: 10.1016/j.neuint.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in microglia morphology and gene expression during normal brain development and in response to hypoxia-ischemia

Abstract: Background: Neuroinflammation plays an important role in ischemic brain injury and recovery, however the interplay between brain development and the neuroinflammatory response is poorly understood. We previously described age-dependent differences in the microglial response and the effect of microglial inhibition. Here we investigate whether age-dependent microglial responses may be related to pre-injury developmental differences in microglial phenotype.Methods: Measures of microglia morphology were quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 70 publications
(102 reference statements)
3
28
0
Order By: Relevance
“…In our study, HI insult resulted in an increased expression of Iba-1 and a change in microglial morphology from branch to ameba-like. These results indicated that cortical microglia were activated after HI, consistent with previous research (Harry, 2013;Cengiz et al, 2019). Microglia can be differentiated into different subtypes after activation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, HI insult resulted in an increased expression of Iba-1 and a change in microglial morphology from branch to ameba-like. These results indicated that cortical microglia were activated after HI, consistent with previous research (Harry, 2013;Cengiz et al, 2019). Microglia can be differentiated into different subtypes after activation.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that microglia are activated in the pathophysiology of HIBD (Ferrazzano et al, 2013;Cengiz et al, 2019), and HMGB1, a pro-inflammatory factor, is upregulated in these activated microglia. Therefore, we explored whether microglial activation was induced in the cerebral cortex after HI.…”
Section: Microglial Activation Occurred In the Cerebral Cortex After Himentioning
confidence: 94%
“…MGs, the major innate immune cells in the brain, are CD11b positive (Li et al, 2017 ) and coexist with another CD11b-positive cell population, MDMs, in developing brain under physiological conditions (Ginhoux et al, 2010 ). Increasing evidence has revealed that the activation patterns of MGs in response to HI differ throughout development (Cengiz et al, 2019 ). However, CD11b + cells are traditionally regarded as MGs even though both MGs and MDMs express CD11b (Denker et al, 2007 ; Su et al, 2019 ; Nishihara et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Those authors found that the subtypes of microglia involved in regulating immunity differed among individuals of different ages and across different brain regions. For example, the expression of genes involved in the signaling pathway downstream of TGF‐β in microglia was recently suggested to be age‐dependent, and signaling through the TGF‐β pathway was increased in P30 mice after H‐I injury compared to P9 mice (Cengiz et al., 2019). Furthermore, according to a study by Lai et al, microglia isolated from embryonic and neonatal brains produced pro‐inflammatory cytokines at higher levels than microglia from brains of other ages (Lai et al., 2013).…”
Section: Maturation‐dependent Topography Of H‐i Injurymentioning
confidence: 99%